Safety and efficacy of elbasvir/grazoprevir in Asian participants with hepatitis C virus genotypes 1 and 4 infection. Issue 9 (17th April 2019) - Wei, Lai; Kumada, Hiromitsu; Perumalswami, Ponni V; Tanwandee, Tawesak; Cheng, Wendy; Heo, Jeong; Cheng, Pin‐Nan; Hwang, Peggy; Mu, Sheng Mei; Zhao, Xu Min; Asante‐Appiah, Ernest; Caro, Luzelena; et al.
Abstract: Background and Aim: Estimates suggest that in Asia, more than 31 million individuals have hepatitis C virus infection. The present analysis was conducted to assess the efficacy and safety of elbasvir/grazoprevir in Asian participants enrolled in the elbasvir/grazoprevir phase 2/3 clinical trials. Methods: This is an integrated analysis of data from 12 international phase 2/3 clinical trials. Asian participants with chronic hepatitis C virus genotype 1 or 4 infection who received elbasvir 50 mg/grazoprevir 100 mg once daily for 12 weeks or elbasvir/grazoprevir plus ribavirin for 16 weeks were included in this analysis. The primary end point was sustained virologic response at 12 weeks after completion of therapy (SVR12). Results: Seven hundred eighty Asian participants from 15 countries were included in this analysis. SVR12 was achieved by 756/780 (96.9%) of all participants, including 748/772 (96.9%) of those who received elbasvir/grazoprevir for 12 weeks and 8/8 (100%) of those who received elbasvir/grazoprevir plus ribavirin for 16 weeks. In the genotype 1b‐infected population, the SVR12 rate was 691/709 (97.5%), and there was no impact of age, high baseline viral load, or presence of cirrhosis. The most frequently reported adverse events were nasopharyngitis (8.0%), upper respiratory tract infection (5.4%), and diarrhea (5.2%). Twenty participants receiving elbasvir/grazoprevir for 12 weeks reported a total of 25 serious adverse events, and 7 (0.9%) discontinued treatment because of an adverse event. Conclusion: Elbasvir/grazoprevir administered for 12 weeks is an effective and generally well‐tolerated treatment option for Asian individuals with hepatitis C virus genotype 1b infection.